EVALUASI PENERIMAAN, PENGGUNAAN, DAN KEPUASAN PENGGUNA TERHADAP WEBSITE PEJABAT PENGELOLA INFORMASI DAN DOKUMENTASI UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA MENGGUNAKAN MODEL UTAUT DAN END-USER COMPUTING SATISFACTION (EUCS) - Eliana Rosa Evelyn (2023)
UPN Veteran Jakarta has implemented a technology-based PPID in the form of a website to fulfill (UU) Number 14 of 2008 concerning public information disclosure. website was released in 2018 so it can still be said to be new. From the results of interviews with several UPN Veterans Jakarta residents who have used website , there are still some deficiencies that need to be corrected. Therefore the authors conducted research to see the acceptance, use, and user satisfaction on the website using 2 methods, namely the UTAUT model and End-User Computing Satisfaction. This study used the PLS-SEM method to evaluate data from 96 respondents who had been obtained and to determine the number of respondents using the Rao Ancient formula and data processing using the SPSS and SmartPLS 4 applications. There were 3 hypotheses rejected and 7 hypotheses accepted. Three hypotheses were rejected, namely Performance Expectancy (PE), Effort Expectancy (EE), and Social Influence (SI) which had a positive but not significant effect website sustainable Behavioral Intention to Use the System (BIUS). 7 hypotheses are accepted, namely Facilitating Condition (FC) has a significant positive effect on continuous use (BIUS), Content, Accuracy, Format, Ease of Use, and Timeliness has a significant positive effect on user satisfaction (US), the last is User Satisfaction ( US) or user satisfaction has a significant positive effect on the continued use of a system or Behavioral Intention to Use the System (BIUS). From this description, it can be said that users of website are still dissatisfied with the acceptance, use, and user satisfaction of the UPN Veteran Jakarta PPID website.